Navigating values in decision-making to shape the landscape of Bangkok’s urban waterways - Wanida Numsuk; Nicola Dempsey (Landscape Research, 2025)
Urban waterways are complex and vulnerable landscapes, particularly in rapidly urbanising cities where they are prone to flooding and degradation of cultural heritage. This complexity is reflected in decision-making processes about urban waterways, as they cross administrative boundaries and involve stakeholders from multiple disciplines who value the urban waterways in different ways. This paper aims to examine how fragmented decision-making contributes to the vulnerability of urban waterways. Focusing on the case of Bangkok, the research engaged those government agencies responsible for the city’s waterways in collaborative workshops to collectively explore their values in decision-making processes. Findings show that practitioners and policymakers expressed differences in values about BUW, which explains the inertia of current waterways management in Bangkok. Findings also show that individually expressed expertise and values can be collectively expressed, demonstrating how collaboration can lead to comprehensive solutions to managing complex environmental challenges in vulnerable urban landscapes.
Keywords: Water Governance and Infrastructure; Urban Planning and Governance; Urban Planning and Landscape Design